Predicting helping behaviors: the role of gender and instrumental/expressive self-schemata. - Belansky, Elaine S.; Boggiano, Ann K. (Sex Roles, 1994)
In this study, the relationships among gender, instrumental/expressive self-schemata, and modes of helping were explored. During session one, the level of schematicity of 114 predominantly white undergraduate subjects was assessed using Spence and Helmreich's Personal Attributes Questionnaire (PAQ), along with importance ratings of the PAQ items to subjects' self-descriptions. During session two, a week later, the same subjects read nine scenarios involving a friend in need of help. Subjects were presented with problem-solving and nurturing behavior items and were asked to rate how likely they were to help the friend. The data support Eagly and Crowley's (1986) social role theory but give little support to Markus' (1977) self-schema theory. Findings indicated that overall, women were more likely to help than men. Additionally, women were more likely to help in a nurturant way than in a problem-solving way, whereas men did not differ in helping modes. Schematicity was not predictive of schema-relevant helping behavior when controlling for gender. The findings of this study imply that in circumscribed contexts, gender may play a more significant role in likelihood to engage in problem-solving and/or nurturing behaviors than schema per se. Reprinted by permission of the author.